FEATURES OF ADULT EDUCATION CENTERS IN ENGLAND - Anastasiia Fedchyshyna (Неперервна професійна освіта: теорія та практика)
The article reveals the peculiarities of adult education centers in one of the countries of the United Kingdom of Great Britain and Northern Ireland – England, which are based at universities, colleges, charitable organizations, etc. The peculiarities of adult education centers in England were determined and analyzed according to certain structural characteristics: axiological orientation, organizational, methodical and information-content provision of the adult education process. It is noted that the main goals of the institutions that provide non-formal adult education in England are the creation of opportunities for obtaining knowledge, skills, qualifications and retraining; promotion of employment and psychological well-being of the adult population; overcoming the main barriers in the employment process; development of digital skills, provision of an inclusive environment and others. It is noted that education providers in England offer a wide selection of forms of adult education, which contribute to the development of professional and personal skills, career growth; provide continuous professional development, acquisition of practical experience and flexible training. It was determined that among the priority areas of adult education in England there are civic education, futures of education, second higher education, technical and vocational education, liberal adult education, professional education, education policy and others.